2021
DOI: 10.1039/d1ta06308a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanodendritic PdPtCu nanosheets/Ti2CTx–CNT electrocatalysts for low overpotential and long-term stable hydrogen evolution reaction

Abstract: Reducing the overpotential and achieving long-term stability of electrocatalysts are vital for facilitating the catalytic activity of hydrogen evolution reaction (HER). Herein, two-dimensional dendritic PdPtCu nanosheets were prepared and further...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Moreover, Qin and colleagues loaded PdPtCu nanosheets on a Ti 2 CT x -CNT composite support to construct an efficient HER catalyst. 149 The average lateral length of the PdPtCu nanosheets was 45 nm and their shape was an asymmetric snowake with many nano-branches and tiny gaps (Fig. 13f).…”
Section: Strategies For Constructing Mxene-based Multi-metal Noble Me...mentioning
confidence: 98%
“…Moreover, Qin and colleagues loaded PdPtCu nanosheets on a Ti 2 CT x -CNT composite support to construct an efficient HER catalyst. 149 The average lateral length of the PdPtCu nanosheets was 45 nm and their shape was an asymmetric snowake with many nano-branches and tiny gaps (Fig. 13f).…”
Section: Strategies For Constructing Mxene-based Multi-metal Noble Me...mentioning
confidence: 98%
“…Therefore, regulating the nanogeometric morphology of Pd to expose different facets is also an effective method regulate the electronic structure of Pd metal. [90] Lei et al used single-crystal Pd NPs wrapped by controllable sizes or facets for the HMF selective oxidation. [91] The study also found that PdÀ NOs wrapped in {111} facets was more conducive to the oxidation of HMF than PdÀ NCs wrapped in {100} facets (Figure 9), especially in the step of HMFCA À OH oxidation to form FFCA.…”
Section: Pd and Pd Alloysmentioning
confidence: 99%
“…The electronic structure of Pd could change with the change of the exposed facets. Therefore, regulating the nano‐geometric morphology of Pd to expose different facets is also an effective method regulate the electronic structure of Pd metal [90] . Lei et al.…”
Section: Thermochemical Oxidation Of Hmf By Noble Metalsmentioning
confidence: 99%
“…Electrostatic self-assembly and in situ reduction are two common strategies for constructing metal–MXenes hierarchical architectures. 35,36 Compared with a physical combination which usually easily results in shedding and agglomeration, the in situ growth method can not only induce a stronger coupling effect and interfacial charge transfer between catalysts and MXenes, 37 but also provide superior uniform distribution and stability to catalysts. 38 MXenes are suitable substrates for in situ growth engineering of various functional materials owing to their benefits such as a large surface area and abundant functional groups as nucleation sites.…”
Section: Introductionmentioning
confidence: 99%